Consistent Wage Offer and Reservation Wage Distributions - Sattinger, M. (Quarterly Journal of Economics, 1991)
Journal Article Consistent Wage Offer and Reservation Wage Distributions Get access Michael Sattinger Michael Sattinger State University of New York at Albany Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 106, Issue 1, February 1991, Pages 277–288, https://doi.org/10.2307/2937916 Published: 01 February 1991